2014
DOI: 10.1093/rfs/hhu075
|View full text |Cite
|
Sign up to set email alerts
|

Do Individual Investors Treat Trading as a Fun and Exciting Gambling Activity? Evidence from Repeated Natural Experiments

Abstract: We hypothesize that individual investors treat trading as a fun and exciting gambling activity, implying substitution between this activity and alternative gambling opportunities. To examine this hypothesis, we study the lottery jackpots and the trading of individual investors in Taiwan. When the jackpots exceed 500 million Taiwan dollars, the trading volume decreases between 5.2% and 9.1% among stocks preferred by individual investors and between 6.8% and 8.6% among lottery-like stocks. The decline in individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(89 citation statements)
references
References 42 publications
5
81
1
2
Order By: Relevance
“…While it is well known that a large portion of gamblers engage in gambling for fun and excitement (e.g., Binde, 2009, 2013), this also appear to be true of a significant portion of stock traders (Dorn & Sengmueller, 2009; Gao & Lin, 2015; Kumar, 2009; Ladley, Liu, & Rockey, 2016). Dorn and Sengmueller (2009) identified three forms of enjoyment that people derive from trading stock: (a) leisure, (b) aspirations of high payoffs, and (c) sensation seeking, with the latter two types of enjoyment being characterized as “gambling motives.”…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is well known that a large portion of gamblers engage in gambling for fun and excitement (e.g., Binde, 2009, 2013), this also appear to be true of a significant portion of stock traders (Dorn & Sengmueller, 2009; Gao & Lin, 2015; Kumar, 2009; Ladley, Liu, & Rockey, 2016). Dorn and Sengmueller (2009) identified three forms of enjoyment that people derive from trading stock: (a) leisure, (b) aspirations of high payoffs, and (c) sensation seeking, with the latter two types of enjoyment being characterized as “gambling motives.”…”
Section: Resultsmentioning
confidence: 99%
“…Most research has found this impact to be fairly specific to lottery-style stocks having low prices, high volatility, and highly skewed returns. Gao and Lin (2015) demonstrated that when lottery jackpot size in Taiwan was high, stock market trading volume in lottery-type stocks declined by 7%–9%. This same relationship between large lottery jackpots and decreased stock trading volume has also be observed in both the United States and Germany (Dorn et al., 2012), with the impact being specific to small traders, options, and individual stocks (with no impact on bonds, mutual funds, or retirement accounts).…”
Section: Resultsmentioning
confidence: 99%
“…Grinblatt and Keloharju (2009) use receipt of speeding tickets as a proxy for having a sensation-seeking personality and find that sensation-seeking is positively correlated with trading activity. Dorn and Sengmueller (2009) find that individuals who report that they enjoy investing or gambling trade more often, and numerous studies find that lotteries are a substitute for trading in the stock market (Barber et al, 2009a;Dorn et al, 2015;Gao and Lin, 2015).…”
Section: Trading Behaviormentioning
confidence: 99%
“…Grinblatt and Keloharju (2009) use receipt of speeding tickets as a proxy for having a sensation-seeking personality and find that sensation-seeking is positively correlated with trading activity. Dorn and Sengmueller (2009) find that individuals who report that they enjoy investing or gambling trade more often, and numerous studies find that lotteries are a substitute for trading in the stock market (Barber et al, 2009a;Dorn et al, 2015;Gao and Lin, 2015).Although the conclusion that individual investors underperform on average was a consensus view in the literature for a long time, several more recent papers have found that net individual 22 buying of a stock positively predicts its future returns over horizons of a week to a month (Jackson, 2003;Kaniel et al, 2008Kaniel et al, , 2012Barber et al, 2009b;Kelley and Tetlock, 2013) or has no predictive power (Griffin et al, 2003). However, this short-term effect is negative in Asian markets (Andrade et al, 2008;Barber et al, 2009a;Choi et al, 2013).…”
mentioning
confidence: 99%
“…For evidence of investors' preference for gambling and the low-beta anomaly, see Blau, Hsu, and Whitby (2014); Bali, Brown, Murray, and Tang (2015); and . For evidence that investors in emerging markets use the stock market as a gambling substitute, see Gao and Lin (2015). For another reading of the preference-for-gambling hypothesis, see Baker, Bradley, and Wurgler (2011).…”
Section: Low Betamentioning
confidence: 99%